International humanitarian actors and governments in areas of conflict: challenges, obligations, and opportunities. (22nd July 2013) - Harvey, Paul
Abstract : For too long international humanitarian aid has neglected the primary responsibility of the state to assist and protect its citizens in times of disaster. A focus on the role of the state in contexts where governments are active parties to a conflict and are failing to live up to these responsibilities is difficult and underpins many of the recurring dilemmas of humanitarian action. The fundamental principles of humanitarian action should offer a framework for principled engagement with governments in situations of conflict but too often they are still interpreted as shorthand for ignoring governments. Using principles to inform engagement with both states and other international actors engaged in crises could provide a way forward. However, this would need to be a humanitarian agenda that engages with developing country governments, with non‐OECD (Organisation for Economic Co‐operation and Development) donors, and with the stabilisation and security agendas of Western governments, and not one that attempts to ring‐fence an ever‐shrinking isolationist humanitarian space.